“Amuada e orgulhosa”: mulheres casadas na imprensa católica paraense (TEL Tempo, Espaço e Linguagem, 2021)
Based on concepts of Culture and Representation, this study analyzes the representations of female roles in the column “Lady's Costumes” from 1939, present in the Catholic magazine A Palavra de Belém do Pará. and women highlighted in the arguments of the magazine.Keywords: representation, gender, women, press.